THE USE OF SKETCH-TO-STRETCH STRATEGY TO IMPROVE STUDENTS’ LISTENING COMPREHENSION - Rezkhita Dwiana, Nadya (Universitas Indo Global Mandiri, 2023)
This study aimed at investigating whether or not there was any significant difference in listening comprehension achievement between before and after the students were taught by using Sketch-to-Stretch strategy, and to find out whether or not there was any significant difference in listening comprehension achievement between the students who were taught by using Sketch-to-Stretch strategy and those who were not. The population of the study was the eleventh grade students of SMA N 18 Palembang with a total number of 265 students. The two classes were chosen as the samples of the study by using purposive sampling method. In collecting the data, the pre-test and post-test were given to both groups. The data were analysed by using paired samples t-test and independent samples t-test. The results of paired samples t-test showed that the p-value (0.000) was lower than 0.05, therefore the null hypothesis (Ho1) was rejected while the alternative hypothesis (Ha1) was accepted. Thus there was a significant difference in listening comprehension achievement before and after the students were taught by using Sketch-to-Stretch strategy. The results of independent samples t-test showed that p-value (0.000) was lower than 0.05, then the null hypothesis (Ho1) was rejected and the alternative hypothesis (Ha1) was accepted. Thus, there was a significant difference in listening comprehension between the students who were taught by using Sketch-to-Stretch strategy and those who were not. To sum up, Sketch-to-Stretch strategy was effective in improving listening comprehension achievement of the eleventh graders of SMA N 18 Palembang Keywords: listening comprehension achievement, Sketch-to-Stretch strategy